Coupled Mg/Ca and clumped isotope analyses of foraminifera provide consistent water temperatures - Breitenbach, Sebastian Franz Martin; Mleneck-Vautravers, Maryline; Grauel, Anna-Lena; Lo, Li; Bernasconi, Stefano; Mueller, Inigo; Rolfe, James; Gazquez, Fernando; Greaves, Mervyn; Hodell, David (Geochimica et Cosmochimica Acta, 2018)
The reliable determination of past seawater temperature is fundamental to paleoclimate studies. We test the robustness of two paleotemperature proxies by combining Mg/Ca and clumped isotopes (D47) on the same specimens of core top planktonic foraminifera. The strength of this approach is that Mg/Ca and D47 are measured on the same specimens of foraminifera, thereby providing two independent estimates of temperature. This replication constitutes a rigorous test of individual methods with the advantage that the same approach can be applied to fossil specimens. Aliquots for Mg/Ca and clumped analyses are treated in the same manner following a modified cleaning procedure of foraminifera for trace element and isotopic analyses. We analysed eight species of planktonic foraminifera from coretop samples over a wide range of temperatures from 2 to 29C. We provide a new clumped isotope temperature calibrations using subaqueous cave carbonates, which is consistent with recent studies. Tandem Mg/Ca–D47 results follow an exponential curve as predicted by temperature calibration equations. Observed deviations from the predicted Mg/Ca-D47 relationship are attributed to the effects of Fe-Mn oxide coatings, contamination, or dissolution of foraminiferal tests. This coupled approach provides a high degree of confidence in temperature estimates when Mg/Ca and D47 yield concordant results, and can be used to infer the past d18O of seawater (d18Osw) for paleoclimate studies.